ASSOCIATION OF ORAL AND OESOPHAGEAL CARCINOMA WITH TOBACCO - Ghani, Rahman; ullah, Rizwan; Shah, Syed Humayun (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT Thirty-two cases of oro-oesophageal carcinoma were treated in the DHQ Teaching Hospital, Abbottabad, in two years from January 1988 to December 1989. In 100% cases of Oral Carcinoma the relation was positive with tobacco. Where as in 92% cases of oesophageal carcinoma the association with tobacco use was found. The cigarettes and smokeless tobacco used both showed a synergistic affect.